Cultural Entanglements : Langston Hughes and the Rise of African and Caribbean Literature - Graham, Shane (Book collections on Project MUSE., 2020)
"This book explores Langston Hughes' associations with black writers from the Caribbean and Africa for a uniquely transnational approach to the life, work, and influence of this important African American literary figure"--